Determination Of Soil Moisture Content And Density Using Electrical Resistivity Values - Abidin, Mohd Hazreek Zainal (2018)
Geotechnical properties are crucial element in design and construction of civil engineering projects. In the past, geotechnical properties were determined using conventional site investigation technique based on drilling and excavation method. The techniques experienced several limitations due to cost, time and data coverage. Hence, this study established basic geotechnical properties determination (moisture content and density) using correlation of geophysical data, particularly electrical resistivity values. This study was performed on SAND and Silty SAND soil with different degree of denseness via laboratory, miniature model and field testes.